Pedagogical Transformation in Audiovisual-Based Vocal Learning: Evidence from a Pre-Experimental Triangulation Study - Delvia Mona; Yensharti; Mia Fahmiati (Grenek: Jurnal Seni Musik, 2026)
This study examined pedagogical transformation in audiovisual-based vocal learning within digital music education, focusing on reflection, self-directed learning, learning interaction, student engagement, and vocal competence. A pre-experimental one-group pretest-posttest design with a concurrent triangulation approach was used. Thirty-two fifth-semester students completed a 12-week intervention involving vocal technique videos, self-directed practice through performance recordings, video-based reflection, and synchronous and asynchronous feedback. Data were collected using a pedagogical transformation instrument and objective vocal competence assessments by two independent evaluators. Analysis applied paired-samples t-tests, Cohen’s d, and Pearson correlation. Results showed significant improvements in all pedagogical indicators and vocal competence dimensions (p < .001). Reflection showed the largest gain (d = 2.13), followed by self-directed learning (d = 1.87). Changes in pedagogical indicators correlated strongly with vocal competence development (r = .74, p < .001). The findings highlight reflection, self-directed learning, and engagement as key dimensions in digital vocal learning.